The role of moral disengagement and authoritarian parenting style towards cyberbullying attitude among social media users - Rahmawati, Nabilla Putri; Virlia, Stefani (University of Muhammadiyah Malang, 2023)
The increase in internet users and the lack of ethics in using the internet have become one of the phenomena that trigger cyberbullying on social media among adolescents. Various internal and external factors can influence cyberbullying attitudes, including moral disengagement and authoritarian parenting style. This study examines the role of moral disengagement and authoritarian parenting style towards cyberbullying attitudes in social media users. The participants in this study were 271 junior high school students aged 12-15 years, accessing social media for more than 2 hours a day and living with both parents. The data collection method used a survey by distributing questionnaires to junior high schools in Surabaya. The scales used were Cyberbullying Attitudes, Moral Disengagement Scale, and Authoritarian Parenting Style (PAQ). The data analysis technique used multiple regression analysis. Reporting multiple regression results in the role of moral disengagement and authoritarian parenting style towards cyberbullying attitudes, R²=0.434, F(102.626), p<0.001 from the mother side and R²=0.432, F(102.003), p<0.001 from father side. However, in this study, 43% contribution comes from moral disengagement, and the authoritarian parenting style has no effect, considering that research participants are individuals in the stage of social identity confusion, so the role of peers could be more influential.